Discovery of a novel ROCK2 inhibitor with anti-migration effects via docking and high-content drug screening. Issue 9 (29th June 2016) - Chong, Cheong-Meng; Kou, Man-Teng; Pan, Peichen; Zhou, Hefeng; Ai, Nana; Li, Chuwen; Zhong, Hai-Jing; Leung, Chung-Hang; Hou, Tingjun; Lee, Simon Ming-Yuen
Abstract : Through the combined virtual and high content drug screening, BIPM was identified as a novel and potent ROCK2 inhibitor. Exposure of SH-SY5Y cells to BIPM led to significant changes in neurite length, cell migration and actin stress fibers via mediating ROCK2 downstream proteins. Abstract : Rho-associated protein kinase (ROCK) mediated the reorganization of the actin cytoskeleton and has been implicated in the spread and metastatic process of cancer. In this study, structure-based high-throughput virtual screening was used to identify candidate compounds targeting ROCK2 from a chemical library. Moreover, high-content screening based on neurite outgrowth of SH-SY5Y cells (a human neuroblastoma cell line) was used for accelerating the identification of compounds with characteristics of ROCK2 inhibitors. The effects of bioactive ROCK2 inhibitor candidates were further validated using other bioassays including cell migration and wound healing in SH-SY5Y cells. Through the combined virtual and high-content drug screening, the compound 1, 3-benzodioxol-5-yl[1-(5-isoquinolinylmethyl)-3-piperidinyl]-methanone (BIPM) was identified as a novel and potent ROCK2 inhibitor. Exposure of SH-SY5Y cells to BIPM led to significant changes in neurite length, cell migration and actin stress fibers. Further experiments demonstrated that BIPM was able to significantly inhibit phosphorylation of cofilin, a regulatory protein of actin cytoskeleton. These results suggest that BIPM could be considered as a promising scaffold for the further development of ROCK2 inhibitors for anti-cancer metastasis.